Advances in anti-tumor based on various anaerobic bacteria and their derivatives as drug vehicles - Song, Daichen; Yang, Xiaofan; Chen, Yanfei; Hu, Pingping; Zhang, Yingying; Zhang, Yan; Liang, Ning; Xie, Jian; Qiao, Lili; Deng, Guodong; Chen, Fangjie; Zhang, Jiandong (Frontiers in Bioengineering and Biotechnology, 2023)
Cancer therapies, such as chemotherapy and radiotherapy, are often unsatisfactory due to several limitations, including drug resistance, inability to cross biological barriers, and toxic side effects on the body. These drawbacks underscore the need for alternative treatments that can overcome these challenges and provide more effective and safer options for cancer patients. In recent years, the use of live bacteria, engineered bacteria, or bacterial derivatives to deliver antitumor drugs to specific tumor sites for controlled release has emerged as a promising therapeutic tool. This approach offers several advantages over traditional cancer therapies, including targeted drug delivery and reduced toxicity to healthy tissues. Ongoing research in this field holds great potential for further developing more efficient and personalized cancer therapies, such as E. coli, Salmonella, Listeria, and bacterial derivatives like outer membrane vesicles (OMVs), which can serve as vehicles for drugs, therapeutic proteins, or antigens. In this review, we describe the advances, challenges, and future directions of research on using live bacteria or OMVs as carriers or components derived from bacteria of delivery systems for cancer therapy.